1999
DOI: 10.1002/(sici)1096-9128(19991225)11:15<887::aid-cpe459>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Managing clusters of geographically distributed high-performance computers

Abstract: We present a software system for the management of geographically distributed highperformance computers. It consists of three components: 1. The Computing Center Software (CCS) is a vendor-independent resource management software for local HPC systems. It controls the mapping and scheduling of interactive and batch jobs on massively parallel systems; 2. The Resource and Service Description (RSD) is used by CCS for specifying and mapping hardware and software components of (meta-)computing environments. It has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In both cases, jobs are routed (migrated) towards the clusters' LRMSs. The Hierarchical 2-level metascheduler is the most encountered variant [8,11]. Distributed meta-scheduler: similarly to the independent clusters architecture, each cluster has its LRMS, and jobs arrive at the individual clusters' LRMSs.…”
Section: Independent Clusters: (Included For Completeness)mentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases, jobs are routed (migrated) towards the clusters' LRMSs. The Hierarchical 2-level metascheduler is the most encountered variant [8,11]. Distributed meta-scheduler: similarly to the independent clusters architecture, each cluster has its LRMS, and jobs arrive at the individual clusters' LRMSs.…”
Section: Independent Clusters: (Included For Completeness)mentioning
confidence: 99%
“…Completely decentralized systems can be scalable and fault-tolerant, but they can be much less efficient than their hierarchical alternatives. While many solutions have already been proposed [4,8,9,11,31,33,34], none has so far managed to achieve acceptance in the grid world, in part because they have yet to prove that they can yield significant benefits when managing typical grid workloads.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand requirements from the application are specified. Advanced reservations and information about future resource usage are mandatory to guarantee that a multi-site [2,6] application starts synchronously. Only a minority of the available resource management systems provide these features.…”
Section: Introductionmentioning
confidence: 99%
“…The support of multi-site parallel execution [12,13,14,15,16] on a computational grid has been examined in previous works, concerning the execution of a job in parallel at different sites. Under the condition of a limited communication overhead, the results from our previous work [10] and from [1,3,4] all showed that multi-site parallel execution can improve the overall average response time.…”
Section: Related Workmentioning
confidence: 99%